Sedum pyriseminum (Crassulaceae), a morphologically remarkable new annual species from the state of Durango, Mexico - Pérez-Calix, Emmanuel (Phytotaxa, 2016)
Mexico is a proven centre of diversity and endemism for Sedum L. (Crassulaceae) and species new to science are continually being discovered. Sedum pyriseminum E. Pérez-Calix is described and illustrated based on specimens originating from the Mexiquillo region, Durango, Mexico. Sedum pyriseminum E. Pérez-Calix is a small annual plant, 2 cm or less in height. Although other Sedum species with this habit are known, S. pyriseminum does not closely resemble any of them. It is most similar to S. vinicolor S. Watson (= S. forreri E. L. Greene), with which it could be confused as a consequence of their similar size and sympatric distribution. The conservation status of Sedum pyriseminum is assessed as Vulnerable (VU).